Graphene/Sulfur Composites with a Foam‐Like Porous Architecture and Controllable Pore Size for High Performance Lithium–Sulfur Batteries. Issue 10 (15th September 2016) - Deng, Wei; Zhou, Xufeng; Fang, Qile; Liu, Zhaoping
Abstract: 3D macroporous graphene foams are extensively used as sulfur supports for high‐performance lithium–sulfur batteries owing to their high electrical conductivity and porous structures. Herein, we investigate the electrochemical properties of foam‐like porous‐graphene‐supported sulfur with two distinctive pore sizes as a cathode material in lithium–sulfur batteries. The smaller pore size (∼500 nm) remarkably increases the electron pathways to facilitate fast electron transport and alleviate polarization of electrodes during charge–discharge processes, and relatively abundant graphene cages in porous graphene with smaller pore size spatially inhibit the shuttle of polysulfides into the electrolyte. Meanwhile, the high specific surface area and pore volume arising from small pores are beneficial for ultrathin sulfur layer deposition on the graphene surface, which effectively alleviates the formation of Li2 S deposition composites and physically suppresses the dissolution of polysulfides. Consequently, the foam‐like graphene/sulfur composite cathode with small pore size and high sulfur content (65 wt %) displays higher specific capacity, better rate capability and cycling stability than those of the samples with larger pores. It can retain a high reversible capacity of 606.7 mAh g −1 after 300 charge–discharge cycles at 1C with 99.0 % Coulombic efficiency. Abstract : Foam‐like porous graphene with controllable pore size is used to investigate the relationship between pore size and electrochemical performance in Li‐S batteries. The smaller pore size (∼500 nm) remarkably increases the electron pathways to facilitate fast electron transport and alleviate polarization of electrodes.